ANTI-CORRUPTION POLICIES AND THEIR IMPLICATIONS FOR NATIONAL POLITICAL STABILITY - Miranu Triantoro; Iyad Abdallah Al- Shreifeen; Hadenan Towpek; Mohd Syahrin (Adisam Publisher, 2025)
Corruption has been one of the most serious problems faced by various countries around the world, and Indonesia is no exception. This phenomenon not only has a major impact on the economy of a nation, but also significantly affects domestic political stability. The research method utilizes literature review as the source of data. The results of the study reveal that the Indonesian government has implemented various anti-graft policies, including the establishment of the Corruption Eradication Commission (KPK), strengthening the judicial system, and increasing transparency in state financial management. The implementation of these policies has had a positive impact on efforts to fight corruption, but has also created various challenges and political dynamics. The implications of anti- corruption policies for domestic political stability can be observed in several ways; Increased public trust in the government and state institutions, Changes in power dynamics and political competition among elites, Strengthening the system of checks and balances in governance, Increased international pressure and its influence on diplomatic relations and Resistance from groups that feel threatened by anti-corruption policies.